Optical gas sensing of sub‐ppm SO2F2 and SOF2 from SF6 decomposition based on photoacoustic spectroscopy. Issue 6 (11th August 2022) - Zhang, Ying; Wang, Mingwei; Yu, Pengcheng; Liu, Zhe
Abstract: SF6 has been recognized worldwide as the main insulating gas for Gas‐Insulated Switchgear (GIS). It is often required to accurately and effectively detect typical SF6 decomposition. In this paper, a sub‐ppm‐level SO2 F2 and SOF2 gas sensor based on photoacoustic spectroscopy (PAS) is proposed and demonstrated. The steel resonant photoacoustic cell with a resonant frequency of 1750 Hz was designed and fabricated. The harmonic detection technique in wavelength modulation spectroscopy was applied to improve the signal‐to‐noise ratio. A mercury‐cadmium‐telluride photodetector was added in the PAS system to monitor the input optical power, in order to compensate for the errors caused by power fluctuations. SO2 F2 and SOF2 were measured by using distributed feedback quantum cascade lasers at 6648 and 7463 nm, respectively. The results show that the proposed sensor performed with favourable linearity within the dynamic range, and reached the minimum detection limit of 0.22 ppm for SO2 F2 and 0.28 ppm for SOF2, which indicated its great potential for monitoring the decomposition process of SF6 in GIS.